Netter’s Sports Medicine 2nd Edition - Lorprayoon, Ead (The Bangkok Medical Journal, 2017)
This book features 8 sections: care of the athletes, special population, conditioning, environment, psychology, medical problems, injuries and specific sports. There are many topics included in each section. There are one or more authors for each subject and they are all known experienced experts in their field. Many new and innovative areas of interest have been included in this second edition which are not featured in the first edition such as: sports pharmacology of chronic diseases, psychiatry and behavioral medicine, the wilderness athlete and adventurer, travel considerations for athletes and sports medical teams, ECG interpretation in athletes, sports ultrasound, the ultimate frisbee and extreme athletes.